2014
DOI: 10.1007/s10812-014-9967-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Natural Radionuclides in Vegetables by Gamma Spectrometry

Abstract: This article reports the activity of natural radionuclides uranium, thorium, and potassium, in different vegetables in Malaysia, measured with a p-type high-purity germanium detector (HPGe). Potassium radionuclides were the most prevalent element in the tested samples, whose activity ranges from 138.89 to 2660.31 Bq/kg. Meanwhile, the activity of uranium was found to be within the minimum detection limit (MDL) to 46.94 Bq/kg, and thorium from Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Variations in the values of the ELCR due to ingestion of fruits are due to the different conversion factors for different age category. This is in agreement with Priharti, et al [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Also the internal hazard index for all the fruits from different states in Niger Delta showed that the internal hazard due to Apricot is very high.…”
Section: Discussionsupporting
confidence: 86%
“…Variations in the values of the ELCR due to ingestion of fruits are due to the different conversion factors for different age category. This is in agreement with Priharti, et al [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Also the internal hazard index for all the fruits from different states in Niger Delta showed that the internal hazard due to Apricot is very high.…”
Section: Discussionsupporting
confidence: 86%
“…From eleven different countries, 58 types of vegetables have been studied with seven common types namely spinach, carrot, cucumber, tomato, pumpkin, green bean and potato [6][7][8][9][10][11][12][13][14][15][16]. However in Malaysia, only 16 types of vegetables have been studied with spinach and cucumber as the common type [17,18]. Studies conducted in ten different countries reported that 26 types of fruits have been studied with eight common types namely apple, pear, orange, mango, banana, papaya, grapes and watermelon [6][7][8][9][10][11][12][13][14][15][16].…”
Section: -2506mentioning
confidence: 99%
“…The research on activity and the mobility of natural radionuclide in the environment is very important in several scientific fields. In Malaysia, only a little record of radioactive contamination of the environment has been reported [9][10][11]. Recently, the transfer of natural radionuclides from soil to groundnut crops has been investigated [12].…”
Section: Introductionmentioning
confidence: 99%